2004
DOI: 10.1023/b:cosu.0000045707.37815.d1
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguities, Awareness and Economy: A Study of Emergency Service Work

Abstract: This paper derives from a study undertaken at an emergency service centre in Sweden. The studies have focused on features of work familiar to the CSCW community, including the documenting and analysing current work practices, understanding the properties of the technology in question, and perhaps most importantly how the technology functions in and through use. Our focus in this paper exemplifies these themes through the analysis of two cases. In the first, the issue in question is the way in which an emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 14 publications
0
47
0
Order By: Relevance
“…In our home discipline of Human-Computer Interaction there have been studies of emergency call centers and hurricane crisis management centers [3,10,15,22], and technology-focused studies of how ubiquitous computing systems [7,8], interactive large screen displays [8,17,19], and simulations [9,11] can improve performance. Obviously, the view of emergency planning and management as high-tech professional work is important, but we would argue that it is not comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…In our home discipline of Human-Computer Interaction there have been studies of emergency call centers and hurricane crisis management centers [3,10,15,22], and technology-focused studies of how ubiquitous computing systems [7,8], interactive large screen displays [8,17,19], and simulations [9,11] can improve performance. Obviously, the view of emergency planning and management as high-tech professional work is important, but we would argue that it is not comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the interdependency between tasks, the more important coordination becomes. Artman and Waern (1999) and Petterson et al (2004) have described how call takers and dispatchers in emergency response teams create common ground with callers and response personnel. For unmanned space exploration, research teams with relative low task interdependency were found to benefit from simultaneous access to real-time data, as more people could participate in the collaboration and scientists could adapt their models based on real-time data (Olson and Olson 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We have something to learn about those occasions upon which awareness is relevant and those where it is not.'' (Pettersson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%